Fabrication of Sb2S3/Sb2Se3 heterostructure for potential resistive switching applications - Pukhraj Prajapat; Pargam Vashishtha; Preeti Goswami; Govind Gupta (Nano Express, 2024)
The exponential growth of large data and the widespread adoption of the Internet of Things (IoT) have created significant challenges for traditional Von Neumann computers. These challenges include complex hardware, high energy consumption, and slow memory access time. Researchers are investigating novel materials and device architectures to address these issues by reducing energy consumption, improving performance, and enabling compact designs. A new study has successfully engineered a heterostructure that integrates Sb _2 Se _3 and Sb _2 S _3 , resulting in improved electrical properties. This has generated significant interest in its potential applications in resistive switching. In this study, we have demonstrated the fabrication of a device based on Sb _2 S _3 /Sb _2 Se _3 heterostructure that exhibits resistive switching behavior. The device has different resistance states that can be switched between high and low resistance levels when exposed to an external bias (−1 V to 0 V to 1 V). It also has good non-volatile memory characteristics, including low power consumption, high resistance ratio (∼10 ^2 ), and reliable endurance (∼10 ^3 ). The device enables faster data processing, reduces energy consumption, and streamlines hardware designs, contributing to computing advancements amidst modern challenges. This approach can revolutionize resistive switching devices, leading to more efficient computing solutions for big data processing and IoT technologies.